Online-Assisted Survey on Antibiotic Use by Pet Owners in Dogs and Cats - Clara Rocholl; Yury Zablotski; Bianka Schulz (MDPI AG, 2024)
The aim of the study was two-fold: first, to collect data on the use of antibiotics in Germany for dogs and cats and, second, their owners' experiences and opinions. Using an anonymous online survey, dog and cat owners were asked about the last antibiotic administration in their pet. The inclusion criterion was any antibiotic administration within the last year. A total of 708 questionnaires from 463 dogs and 245 cats could be evaluated. Diarrhea was reported as the most common reason for antibiotic administration in dogs (18.4%). Wound infection/abscess/bite injury was the second most common reason in dogs (16.0%). In cats wound infection/abscess/bite injury was the most common reason (23.3%), followed by dental treatment (21.2%) and upper respiratory tract infections (16.7%). The most common antibiotics used systemically in both species were amoxicillin/clavulanic acid (32.5%), amoxicillin (14.8%), metronidazole (6.9%), and doxycycline (6.8%). While efficacy (99.9%) and tolerability (94.8%) were rated as most important for the choice of antibiotics, costs (51.6%) were cited as predominantly unimportant. First-line antibiotics were used significantly more often than critically important antibiotics. The majority of animal owners show awareness for avoidance of antibiotic resistance and the use of critically important antibiotics.